Possible Pathways of Disease Communication of the Endo-Perio Lesions and their Management - Gopal Krishna Choudhury1, Sangram Panda2, Mirna Garahnayak3, Abhilash Mohapatra3, Pradyumna Sahoo2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The periodontal therapy deals with all the aspects of a periodontium as a whole including both theprevention and repair. Whereas the endodontic therapy deals with only the pulp and the periapical tissues.The relationship among the periodontal and endodontic disease has remain always a controversial part inthe dentistry. However, to have the accurate treatment, a practitioner must possess a very sound knowledgeof all the possible pathways of communication of an endo-perio lesion. Hence, this review paper aims atpresenting the possible pathways of communication for the endo-perio lesions at a simpler way to help theclinician in their daily basis of perio-endo management.